Critical applications in vehicular ad hoc/sensor networks - Kumar, Neeraj; Pathan, Al-Sakib Khan; Duarte Jr., Elias. P.; Shaikh, Riaz Ahmed (Springer, 2014)
Vehicular ad hoc networks (VANETs) have emerged as a promising technology with several applications that may have a deep impact on our society. In the past few years, we have witnessed a tremendous growth in this field, with several new techniques and standards having been proposed with the objective of making it easier and safer to drive and transport passengers. Diverse applications are already available that provide information on traffic conditions, the density of vehicles, duration of traffic lights, among many other variables that allow smarter driving decisions to be taken. Moreover, drivers and passengers can download and upload this information as they travel, with the aid of the Road Side Units (RSUs), some of which are already deployed. RSUs are usually connected to the Internet, and are thus widely available to users and services.